The Communism of Thought - Munro, Michael (punctum books, 2014)
The Communism of Thought takes as its point of departure a passage in a letter from Dionys Mascolo to Gilles Deleuze: "I have called this communism of thought in the past. And I placed it under the auspices of Hölderlin, who may have only fled thought because he was unable to live it: 'The life of the spirit between friends, the thoughts that form in the exchange of words, by writing or in person, are necessary to those who seek. Without that, we are by our own hands outside thought.'" What, in light of that imperative, is a correspondence? What is given to be understood by the word, let alone the phenomenon? What constitutes a correspondence? What occasions it? On what terms and according to what conditions may one enter into that exchange "necessary," in Hölderlin's words, "to those who seek"? Pursuant to what vicissitudes may it be conducted? And what end(s) might a correspondence come to have beyond the ostensible end that, to all appearances, it (inevitably) will be said to have had?